2018
DOI: 10.3390/nu10111645
|View full text |Cite
|
Sign up to set email alerts
|

Potential Prebiotic Properties of Nuts and Edible Seeds and Their Relationship to Obesity

Abstract: Obesity is a global epidemic chronic condition and is progressing at a rapid rate. This review focuses on the potential prebiotic properties of nuts and edible seeds and the plausible mechanisms that their consumption may help the prevention and the management of overweight and obesity. The literature review was performed by searching papers about the topic in MEDLINE and SCOPUS databases. The healthy attributes of nuts and edible seeds, especially dietary fibers and polyphenols contents, indicate that their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 56 publications
0
21
0
4
Order By: Relevance
“…Nuts such as almonds are rich sources of fiber, unsaturated fats, and polyphenols (6), all nutrients that can favorably alter the gut microbiome (7–9). Differences in relative abundance of specific bacterial taxa have been observed with varying doses of almonds and pistachios (42 g or 84 g) (10), different almond processed forms (42 g) (11), and walnut (42 g) (12) consumption over short periods (<3 wk).…”
Section: Introductionmentioning
confidence: 99%
“…Nuts such as almonds are rich sources of fiber, unsaturated fats, and polyphenols (6), all nutrients that can favorably alter the gut microbiome (7–9). Differences in relative abundance of specific bacterial taxa have been observed with varying doses of almonds and pistachios (42 g or 84 g) (10), different almond processed forms (42 g) (11), and walnut (42 g) (12) consumption over short periods (<3 wk).…”
Section: Introductionmentioning
confidence: 99%
“…A major difference was that we used almond to replace carbohydrate. Almond as a commonly eaten nut, is a rich source of dietary fiber, polyphenols, and unsaturated fatty acids [ 44 ], that may be protective against the development of depression [ 45 , 46 , 47 ]. With regard to the association of nuts intake and mental health, most of studies showed the positive effect of nuts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the potential for intrinsic kernel quality has gained attention with the aim of promoting nut consumption 12 , 13 . The nutritional properties of hazelnut and its health benefits, related to the richness of high‐value fatty acids and natural antioxidants, have been emphasized 14–16 . Among the main chemical components in the kernel, lipids are regarded as the constituent that makes a major contribution to the quality and storability of nuts and derived products 17 – 20 .…”
Section: Introductionmentioning
confidence: 99%